TINJAUAN KRITIS TERHADAP HAK-HAK PEREMPUAN DALAM UU. NO. 1 TAHUN 1974 TENTANG PERKAWINAN: UPAYA MENEGAKKAN KEADILAN DAN PERLINDUNGAN HAM PERSPEKTIF FILSAFAT HUKUM ISLAM - Asnawi, Habib Shulton (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2016)
The scientific by the fact injustice, discrimination, subordinated, depolitisasi and hak-hak violation of human rights ( HAM ) Women. This was caused by some of the articles in law . No. 1 in 1974 about the marriages ( UPP ). This study draw in terms of perspektif- approach \ philosophy islamic law ( FHI). Focus this writing: ( 1 ). How raights women in philosophy UPP perspective islamic law ? (2). What are the injustice and human rights violations women perspective philosophy islamic law?. This research is research library, review of critical thinking normativ and sociological implications, by using the method diskriftif, critical analysis, progressive. Scientific conclusions writing this is women experienced form injustice and human rights violations and some article in UPP declared contrary to the purpose of Islamic law namely the principle of maqasyid as-syari ah (kemashlahatan, justice and the protection of human rights). His discoveries in this writing is that country had violated a commitment to an agreement the united nations, because indonesia did not practice principles which is in the convention cedaw. And indonesia ratified convention cedaw through law No. 7 1984 regarding the ratification of the removal of all forms of discrimination against women.